Study of the pharmacokinetics of polymerized porcine hemoglobin (pPolyHb). (3rd October 2018) - Shen, Yuesheng; Zhu, Wenjin; Zhao, Mengye; Zhao, Guige; Niu, Geng; Bai, Yuwei; Yang, Bo; Chen, Chao; Zhu, Hongli
Abstract: Polymerized porcine hemoglobin (pPolyHb), a kind of glutaraldehyde-polymerized haemoglobin-based oxygen carrier, was developed as a potential red blood substitute for clinical applications. Assessment of its absorption, distribution, and metabolism is a major determinant of its safety and efficacy. In this study, a series of pharmacokinetic parameters of pPolyHb were measured and calculated in different animal models, such as the top-load model, the 50% exchange transfusion model and the haemorrhagic shock model. The results showed that the kinetic process of pPolyHb in rats conforms to the laws of linear pharmacokinetics in vivo . The half-life of pPolyHb was superior and more stable under non-pathological conditions, but in clinical situations such as trauma and anaemia, the half-life of pPolyHb may decline. The study of clearance (CL) and the apparent volume of distribution (Vd) of pPolyHb in these three different animal models demonstrated longer residence and a predominant, targeted role of pPolyHb with little accumulation in tissues. Through this study, the superior pharmacokinetic characteristics of pPolyHb have been proved and will aid in the determination of a reasonable dosing regimen and administration interval in clinical situations.